Formulation of community driven business strategies for MSMEs using SWOT and QSPM - Musa Mulyadi; Yudha Heryawan Asnawi; Heny Kuswanti Daryanto (Universitas Ahmad Dahlan, 2026)
This study aims to formulate community-based business strategies for micro, small, and medium enterprises in the garment and doll sectors in Caringin, Bogor, Indonesia. Although micro, small, and medium enterprises in this area have significant potential, many still perform suboptimally despite abundant resources and opportunities. This study uses a qualitative case study design and methodology that combines forum group discussions, questionnaires, and strategic analysis using the strengths, weaknesses, opportunities, threats and quantitative strategic planning matrix. The research sample consists of 13 micro, small, and medium enterprises actors involved in the Caringin micro, small, and medium enterprises forum. The findings indicate that while micro, small, and medium enterprises have significant strengths in skilled labor and the quality of local raw materials, they face challenges in digital marketing, financial management, and limited production capacity. The formulated strategies include enhancing digital literacy, leveraging online platforms for marketing and sales, and developing products that leverage local design differentiation. The theoretical contribution of this study lies in applying participatory development theory to formulate community-based strategies for the micro, small, and medium enterprises sector, particularly in similar regions. Practically, this research provides more relevant and practical strategic guidance for micro, small, and medium enterprises to optimize their potential. This study fills a gap in the existing literature by providing new insights into the role of the community in formulating micro, small, and medium enterprises business strategies.